Insights into cryptochrome modulation of ABA signaling to mediate dormancy regulation in Marchantia polymorpha. Issue 4 (8th March 2023) - Liao, Jiakai; Deng, Ban; Yang, Qixin; Li, Yu; Zhang, Yuxiang; Cong, Jiajing; Wang, Xiaqin; Kohnen, Markus V.; Liu, Zhong‐Jian; Lu, Meng‐Zhu; Lin, Deshu; Gu, Lianfeng; et al.
Summary: The acquisition of dormancy capabilities has enabled plants to survive in adverse terrestrial environmental conditions. Dormancy accumulation and release is coupled with light signaling, which is well studied in Arabidopsis, but it is unclear in the distant nonvascular relative. We study the characteristics and function on dormancy regulation of a blue light receptor cryptochrome in Marchantia polymorpha (MpCRY). Here, we identified MpCRY via bioinformatics and mutant complement analysis. The biochemical characteristics were assessed by multiple protein‐binding assays. The function of MpCRY in gemma dormancy was clarified by overexpression and mutation of MpCRY, and its mechanism was analyzed via RNA sequencing and quantitative PCR analyses associated with hormone treatment. We found that the unique MpCRY protein in M. polymorpha undergoes both blue light‐promoted interaction with itself (self‐interaction) and blue light‐dependent phosphorylation. MpCRY has the specific characteristics of blue light‐induced nuclear localization and degradation. We further demonstrated that MpCRY transcriptionally represses abscisic acid (ABA) signaling‐related gene expression to suppress gemma dormancy, which is dependent on blue light signaling. Our findings indicate that MpCRY possesses specific biochemical and molecular characteristics, and modulates ABA signaling under blue light conditions to regulate gemma dormancy in M. polymorpha .